Rhamnolipid Biosurfactant Recent Trends in Production and Application - Kumar, Rajesh (Springer Singapore, 2018)
This book highlights the recent developments on rhamnolipid biosurfactant, its properties, role on the natural environment and various applications. Recently, it has shown promising application in Environment, Agriculture, food, petroleum, and pharmaceutical industries due to its environment-friendly and easily degradable nature. The book emphasizes on the various techniques that are utilized for the detection and isolation of rhamnolipid biosurfactant from microorganisms. It highlights the various aspects of the rhamnolipid biosurfactants including structural characteristics, production, and its application. The book presents the current knowledge and the latest advances in the function-based metagenomics strategies to facilitate the exploration of the novel biosurfactants.